Implementasi AHP Untuk Sistem Pendukung Keputusan Penentuan Prioritas Pembangunan Infrastruktur Daerah - Wido Purnama; M. Afdal; Inggih Permana; Siti Monalisa (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
BAPPEDA Indragiri Hulu is a governmental organization in Indragari Hulu Regency that aids the government in accomplishing development planning, research, and development-related tasks. However, determining development priorities presents obstacles stemming from the lack of calculation methods and visualization maps to more easily identify the locations of construction sites. To address this issue, a decision support system utilizing the Analytical Hierarchy Process method was constructed. This system considers various criteria, including condition, budget, urgency, usability, and durability, to compare and identify the best development option. Additionally, the system features a Web GIS map visualization function to aid in identifying construction sites. The study found that improving the road in Pematang Rebah City, Rengat Barat District, was the most important alternative, followed by creating box covers for the Tanah Datar Sibabat road in Seberida District and improving roads in Rengat City in Rengat District. This web-based system ranks development priorities and can effectively assist in determining regional development priorities. Based on the results of the Blackbox test, this system is deemed 100% valid, while the User Acceptance Test on this system yields an 81% score, which is highly satisfactory.